Pengaruh Motivasi Kerja dan Etos Kerja Terhadap Efektivitas Kerja Pada PT. Tunas Jaya Sanur Di Denpasar (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
This study aims to analyze the influence of work motivation and work ethic on work effectiveness at PT. Tunas Jaya Sanur in Denpasar. This research uses a quantitative approach with a survey method. The population in this study consists of 150 employees from all departments at PT. Tunas Jaya Sanur. The sampling method used is probability sampling, with only 30% of the population selected as the research sample. The data analysis technique employed is multiple linear regression analysis. The results of the study indicate that work motivation has a positive and significant influence on work effectiveness. Work ethic also has a positive and significant effect on employee work effectiveness.